SEPARATION OF POWERS AS ORDINARY INTERPRETATION - Manning, John F. (Harvard law review, 2011)
The Supreme Court applies the structural provisions of the Constitution by relying on an overarching framework of "separation of powers." Its cases reflect two distinct visions of the doctrine. Functionalist decisions presuppose that Congress has plenary authority to compose the government under the Necessary and Proper Clause, subject only to the requirement that a particular governmental scheme maintain a proper overall balance of power. Formalist opinions, in contrast, assume that the constitutional structure adopts a norm of strict separation which may sharply limit presumptive congressional power to structure the government. This Article contends that, to the extent that these theories each rely on a freestanding separation of powers principle derived from the structure of the document as a whole, both contradict the idea that the Constitution is a "bundle of compromises" that interpreters must respect if they are to show fidelity to the constitutionmaking process. The historical record reveals that the founding generation had no single baseline against which to measure what "the separation of powers" would have required in the abstract. The U. S. Constitution, moreover, not only separates the powers of the three branches, but also blends them in order to provide mutual checks among the branches. In so doing, it strikes many different balances and expresses its purposes at many different levels of generality. When a provision carefully specifies which branch will exercise a given power and in what manner, interpreters must respect that specific compromise by prohibiting alternative means of exercising that power. Conversely, when the Constitution speaks indeterminately to a particular question, constitutionmakers should not rely on abstract notions of separation of powers to displace Congress's assigned power to compose the federal government. Rather than invoking any overarching separation of powers theory, interpreters should apply tools of ordinary textual interpretation to construe the particular clauses that make up the constitutional structure.